Qualitative insights into the experience of teaching shared decision making within adult education health literacy programmes for lower‐literacy learners. (5th July 2017) - Muscat, Danielle M.; Morony, Suzanne; Smith, Sian K.; Shepherd, Heather L.; Dhillon, Haryana M.; Hayen, Andrew; Trevena, Lyndal; Luxford, Karen; Nutbeam, Don; McCaffery, Kirsten J.
Abstract: Background: Enhancing health literacy can play a major role in improving healthcare and health across the globe. To build higher‐order (communicative/critical) health literacy skills among socially disadvantaged Australians, we developed a novel shared decision making (SDM) training programme for adults with lower literacy. The programme was delivered by trained educators within an adult basic education health literacy course. Objective: To explore the experience of teaching SDM within a health literacy programme and investigate whether communicative/critical health literacy content meets learner needs and teaching and institutional objectives. Design and participants: Qualitative interview study with 11 educators who delivered the SDM programme. Transcripts were analysed using the Framework approach; a matrix‐based method of thematic analysis. Results: Teachers noted congruence in SDM content and the institutional commitment to learner empowerment in adult education. The SDM programme was seen to offer learners an alternative to their usual passive approach to healthcare decision making by raising awareness of the right to ask questions and consider alternative test/treatment options. Teachers valued a structured approach to training building on foundational skills, with language reinforcement and take‐home resources, but many noted the need for additional time to develop learner understanding and cover all aspects of SDM. Challenges for adult learners included SDM terminology, computational numerical risk tasks and understanding probability concepts. Discussion and conclusions: SDM programmes can be designed in a way that both supports teachers to deliver novel health literacy content and empowers learners. Collaboration between adult education and healthcare sectors can build health literacy capacity of those most in need.